Laboratory-scale preparation of potentially inexpensive low- and middle-range protein molecular weight markers for SDS-PAGE - Recuenco, Mariam C.; Alejo, Kennethjer G. (2019)
Protein molecular weight (MW) markers for sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) were prepared from proteins extracted and fractionated from egg white, skim milk, porcine serum, and wheat flour. Fractionation methods employed include adsorption on bentonite, isoelectric pH precipitation, ammonium sulfate precipitation, and acetone fractionation. The % recoveries based on reported yields of the egg white proteins ? lysozyme, ovotransferrin, and ovalbumin ? were 9.70%, 116.51%, and 25.34%, respectively. The % recoveries for caseins from skim milk, porcine albumin, and glutenin fraction from wheat were 93.00%, 0.15%, and 0.54%, respectively. Fractions from egg white, caseins, and porcine albumin (EMPA) were combined to prepare the low-range MW marker ? with EMPA consisting of seven proteins and MW range of 11.8?77.1 kDa. The protein fraction from wheat (W) with six components and MW range of 16.2?106.3 kDa was prepared as the middle-range marker (WH). Using a commercial marker as a primary standard, the MWs of the markers? components were established. The prepared markers were then used as standards to estimate the experimental MWs of some common proteins. The experimental MWs were within 1.2?11.0% difference from the experimental MWs calculated from using the commercial marker as standard. The MWs were also within <13% error from the theoretical MWs, with lower % errors for the proteins with MWs within the markers? MW range. While some components ? specifically the egg white proteins ? could be present in their glycosylated forms, both markers showed the ladder profile ? consistently suggesting stability of the components under heating, denaturing, and reducing conditions even with some possible effects of glycosylation on some components. (Author's abstract)